Comparative review of transcortical and trans-Sylvian approaches for surgical resection of giant insular gliomas: outcomes and challenges - Maman Roufai Hamissou Moussa; Rafeq Agila (Egyptian Journal of Neurosurgery)
Abstract The giant insular glioma is defined as occupying all zone of the insula according to the Berger-Sanai classification. It is often encountered with a large volume, extending to the surrounding areas, functional pathway, and vascular structure, making its surgical resection very challenging for a neurosurgeon. In the literature, some studies revealed that it is more likely not to achieve a great extent of resection and is associated with a high postoperative morbidity rate. However, those studies included different insular gliomas regarding the location, extension, and surgical approach addressed. The giant insular gliomas subtype has been reported in the literature combined with all the insular gliomas and different surgical methods, which may bias the outcomes. The main approaches for insular glioma surgery are transcortical (TC) and trans-Sylvian (TS) approaches. This review aims to evaluate the evidence supporting the use of TS and TC surgical approaches for the management of giant insular gliomas. It will also analyze the associated postoperative outcomes to provide insights into their effectiveness and safety.